Evaluation of the stability of a highway slope through numerical modeling (2017)
Mass movement in natural slopes can cause great material and human loss for society. In this context, stability analyses become quite complex since there are a large number of uncertainties involved in the interpretation of the problem. This paper presents an analysis of the stability of a highway slope, located near the city of Guarulhos, in São Paulo, Brazil. The shear strength parameters of the soil and the stratigraphic profile were defined based on the results of Standard Penetration Tests (SPT). The initial factor of safety was below the minimum value recommended by the Brazilian technical standards, but did not indicate imminent failure. However, additional analyses which incorporated the influence of critical periods of rain and probabilistic analysis indicated that the stability of the section was unsatisfactory. Therefore, numerical modeling is shown to be a complex and effective tool for implementation of conventional analyses of slope stability.